2021
DOI: 10.2519/jospt.2021.9707
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Tests of Tibialis Posterior Tendinopathy: Are They Reliable, and How Well Are They Reflected in Structural Changes on Imaging?

Abstract: Clinical Tests of Tibialis Posterior Tendinopathy: Are They Reliable, and How Well Are They Reflected in Structural Changes on Imaging?tendinopathy occurs on a continuum from a disordered tendon to a rupture, can be accompanied with various degrees of joint destruction, 2,13,23 and is the most common cause of acquired flatfoot deformities in adults. 12,18 Tibialis posterior tendinopathy is often misdiagnosed or goes undiagnosed, until significant and prolonged symptoms severely interfere with function. 15,16 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
5
1
1
Order By: Relevance
“…The paper highlighted that, after using clinical findings, a diagnosis can be confirmed with US. However, US and clinical findings on their own are not sufficient [17]. The findings of this paper related to the PTE contradicts the findings of one paper, which found that, compared to magnetic resonance imaging (MRI), PTE had a sensitivity of 86% and a specificity of 100% [26].…”
Section: • Physical Assessmentscontrasting
confidence: 90%
See 3 more Smart Citations
“…The paper highlighted that, after using clinical findings, a diagnosis can be confirmed with US. However, US and clinical findings on their own are not sufficient [17]. The findings of this paper related to the PTE contradicts the findings of one paper, which found that, compared to magnetic resonance imaging (MRI), PTE had a sensitivity of 86% and a specificity of 100% [26].…”
Section: • Physical Assessmentscontrasting
confidence: 90%
“…A combination of tests, such as the SLHR, palpation, swelling, and weakness, have also been compared to MRI and/or US. However, none of the tests have been shown to be 100% effective in the diagnosis of PTTD; therefore, it is advised to use a mixture of MSK assessment and imaging to provide a complete picture of the damage/inflammation present, as well as the functional deficit with which the patient presents [17,29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fiftytwo people participated in the study, they were examined by 2 physiotherapists and an ultrasound examination was performed. The singleleg toeclimb test was best related to imaging findings in people with TPT (tibialis posterior tendinopathy), which is in line with modern thinking about tendinopathy as a clinical picture associated with loading [7]. PTT physiotherapy according to KaKin Ling et al helps in two ways, first, it reduces swelling in acute inflammation, and second, it contributes to strengthening the posterior ti- • gait reeducation,…”
Section: Discussionsupporting
confidence: 62%